The labor market in conditions of war (Economics and region, 2023)
The study is devoted to the issues of the state of the labor market in the conditions of a full-scale war, the identification of its features and recommendations for ensuring the effective functioning of the labor market after the war. It is noted that the war was the cause of the economic recession and caused the increase in the level of unemployment and a sharp reduction in the income of the population. The article provides and analyzes statistical data on the number of refugees abroad since the beginning of the full-scale invasion, their adaptation, employment in other countries, and intentions to return to Ukraine. The influence of internally displaced persons on the labor market was determined: the number of IDPs; the regions from which the most people moved and the regions that received the most people. Factors for the loss of skilled labor are named: migration, internally displaced persons and deaths, which include professionals in such professions as education, science, law, medicine, IT specialists and many others. The wage dynamics and financial stability of companies in the first months of the war were analyzed using the example of small and medium-sized businesses. Analyzed data on the unemployment rate, the number of applicants for 1 vacancy, and the geography of vacancies were reviewed and provided. It was determined that the above-mentioned factors have a negative impact on the labor market and have led to a reduction in domestic consumption and a decrease in the labor force, which in the long term will put pressure not only on the labor market, but also on the pension system of Ukraine and on the potential GDP. Conclusions are made regarding the impact of the war on the labor market, the main factors of pressure on the market activity are determined, and recommendations are proposed that will ensure the effective functioning of the labor market in the post-war period. It is proposed that, in order to restore the labor market after the war, create conditions that will ensure an increase in population employment, stabilization of the labor market, a decrease in the unemployment rate, an increase in the level of productivity in the market, the creation of new jobs, will have an impact on the redistribution of labor between sectors of the economy and will take into account workers with limited opportunities.
Keywords: labor market; war; migration; internally displaced persons; unemployment; wages; enterprise